Development and validation of Biology Interest Instrument (BII) for sustainability of professional teacher education - Reni Marlina; Chokchai Yuenyong; H. Hamdani; Muhammad Saefi; H. Husamah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Biology interest is a defining characteristic that shapes the identity of biology teachers and guides their pedagogical decision-making in the classroom. Recognizing the importance of this attribute in both current and prospective biology teachers, this study aimed to develop and validate the Biology Interest Instrument (BII) to support the sustainability of professional teacher education. The BII was designed to capture five core dimensions: approaches to learning biology, application of biology instruction, assessment practices, teacher characteristics, learning environment, and the nature of the biology curriculum. The development process involved input from biology education experts across 11 Indonesian institutions through focus group discussions. To assess the instrument’s validity and reliability, data were collected from 855 prospective biology teachers and analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The final instrument comprises 32 items across five dimensions, all demonstrating acceptable psychometric properties. The BII is recommended for use in teacher education programs, particularly in Indonesia and other developing countries, to identify and foster biology interest in future educators.